Effects of guanidinoacetic acid supplementation on lactation performance, nutrient digestion and rumen fermentation in Holstein dairy cows. (12th October 2022) - Liu, Yongjia; Zhang, Jing; Wang, Cong; Guo, Gang; Huo, Wenjie; Xia, Chengqiang; Chen, Lei; Zhang, Yawei; Pei, Caixia; Liu, Qiang
Abstract: BACKGROUND: Considering the high energy demand of lactation and the potential of guanidinoacetic acid (GAA) addition on the increase in creatine supply for cows, the present study investigated the effects of 0, 0.3, 0.6 and 0.9 g kg −1 dry matter (DM) of GAA supplementation on lactation performance, nutrient digestion and ruminal fermentation in dairy cows. The study used 40 mid‐lactation multiparous Holstein cows and the study duration was 100 days. Results: DM intake was not affected, but milk and milk component yields and feed efficiency increased linearly with increasing GAA addition. The total‐tract digestibility of DM, organic matter, neutral detergent fibre, acid detergent fibre and non‐fibre carbohydrates increased linearly and that of crude protein increased quadratically with increasing GAA addition. When the addition level of GAA increased, ruminal pH, molar percentages of butyrate, isobutyrate and isovalerate and the acetate‐to‐propionate ratio decreased linearly, and the total volatile fatty acids concentration and propionate molar percentage also increased linearly, whereas the acetate molar percentage and ammonia‐N concentration were unaltered. The activities of fibrolytic enzymes, α‐amylase and protease increased linearly. The populations of total bacteria, fungi, Ruminococcus albus, Fibrobacter succinogenes, Ruminococcus flavefaciens, Ruminobacter amylophilus and Prevotella ruminicola increased linearly, whereas protozoa and methanogens decreased linearly with increasing GAA addition. As for the blood metabolites, concentrations of glucose, urea nitrogen and methionine were unchanged, total protein, albumin, creatine and homocysteine increased linearly, and folate decreased linearly with increasing GAA supply. Conclusion: The results of the present study indicate that supplementation of GAA improved milk performance and rumen fermentation in lactating dairy cows. © 2022 Society of Chemical Industry.